Progress and Challenges of Nonfinancial Defined Contribution Pension Schemes : Volume 2. Addressing Gender, Administration, and Communication - Holzmann, Robert; Palmer, Edward; Palacios, Robert; Sacchi, Stefano (Washington, DC: World Bank, 2019)
This is the third publication to analyze progress, challenges, and adjustment options of this . reform revolution for mandated public pension schemes. The individual account-based but unfunded approach that promises fair and financially sustainable benefits is a reform benchmark for all pension schemes. Nonfinancial defined contribution (NDC) schemes originated in the 1990s independently in Italy and Sweden, were then adopted by Latvia, Poland, and Norway, envisaged but not implemented in various other countries (such as Egypt and Russia), and remain under discussion in many countries across the world (such as China and France). In its complete form, the approach also comprises budget-financed basic income provisions and mandated or voluntary funded provisions.